Effective Operational Improvement for MSMEs: Knowledge Management (KM) Practices – Implementation at Umy Lemon Sukabumi - Budiarti, Isniar; Firmansyah, Deri; Susetyo, Dwinanto Priyo (PT. Riset Press International, 2025)
Rural MSMEs that have products based on local wisdom have the potential to develop in line with the digital economy era that has entered the society 5.0 era. However, apart from the capital aspect, MSME actors are sometimes still lacking focus in developing their businesses, knowledge management (KM) to improve effective operations is still low, affecting low marketing practices that are in line with current trends and have an impact on the sales generated. The implementation of this Community Service (PKM) activity consists of five stages, of which two stages are carried out at the beginning of the activity, one stage as the main pre-activity that accompanies the implementation process and ensures the selection of the activity management model, while the other two stages are the stages of implementing the activity and evaluation at the end, involving the target partner, namely the Umy Lemon Sukabumi MSME. The results and evaluation of activities, feedback from the achievements of the implementation of the activities showed: [1] Umy Lemon MSME actors were able to analyze and combine the three indicators that formed KM, namely the ability to create knowledge, manage and enrich knowledge, share and utilize knowledge to then be implemented and developed in more effective and profitable business operations; [2] improve the understanding of the recording system that emphasizes administrative discipline, the ability to determine the appropriate selling price based on costs, understand the sales recording system and its reporting; [3] able to innovate products; and [4] the growth of adaptive behavior and the ability to expand business reach through business transformation and digitalization practices, namely by implementing online marketing and sales strategies on digital platforms on social media.